2014
DOI: 10.1242/bio.20149092
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte-specific regulation of hMeCP2 expression in Drosophila

Abstract: Alterations in the expression of Methyl-CpG-binding protein 2 (MeCP2) either by mutations or gene duplication leads to a wide spectrum of neurodevelopmental disorders including Rett Syndrome and MeCP2 duplication disorder. Common features of Rett Syndrome (RTT), MeCP2 duplication disorder, and neuropsychiatric disorders indicate that even moderate changes in MeCP2 protein levels result in functional and structural cell abnormalities. In this study, we investigated two areas of MeCP2 pathophysiology using Droso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…Interestingly, astrocyte-specific MECP2 overexpression in Drosophila causes a reduction in the total time spent asleep and induces deficits in sleep maintenance. Defects in sleep behavior are neuropsychological features of RETT, suggesting that abnormal sleep patterns might be caused by MECP2 overexpression in astrocytes [ 139 ]. Through Drosophila disease models, it has been revealed that the ectopic expression of MECP2 induces deficits in neuronal development and behavior, which is regulated by glial cells, especially astrocytes.…”
Section: Drosophila Models Of Human Cns Disordementioning
confidence: 99%
“…Interestingly, astrocyte-specific MECP2 overexpression in Drosophila causes a reduction in the total time spent asleep and induces deficits in sleep maintenance. Defects in sleep behavior are neuropsychological features of RETT, suggesting that abnormal sleep patterns might be caused by MECP2 overexpression in astrocytes [ 139 ]. Through Drosophila disease models, it has been revealed that the ectopic expression of MECP2 induces deficits in neuronal development and behavior, which is regulated by glial cells, especially astrocytes.…”
Section: Drosophila Models Of Human Cns Disordementioning
confidence: 99%
“…Thirteen studies were identified by this systematic search as summarized in Table 1. We categorized the studies into three groups according to the species of animal used for modeling RTT, which were one on cynomolgus monkey (Y. Chen et al., 2017), two on Drosophila (Gupta, Morgan, Bailey, & Certel, 2016; Hess‐Homeier, Fan, Gupta, Chiang, & Certel, 2014), and 10 using mice (D'Cruz et al., 2010; Fuchs et al., 2018; Johnston et al., 2014; Li et al., 2015; Lo Martire et al., 2017; Moretti, Bouwknecht, Teague, Paylor, & Zoghbi, 2005; Ren, Ding, Funk, & Greer, 2012; Robinson, Plano, Cobb, & Riedel, 2013; Tsuchiya et al., 2015; Wither et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Drosophila (Gupta, Morgan, Bailey, & Certel, 2016;Hess-Homeier, Fan, Gupta, Chiang, & Certel, 2014), and 10 using mice (D'Cruz et al, 2010;Fuchs et al, 2018;Johnston et al, 2014;Li et al, 2015;Lo Martire et al, 2017;Moretti, Bouwknecht, Teague, Paylor, & Zoghbi, 2005;Ren, Ding, Funk, & Greer, 2012;Robinson, Plano, Cobb, & Riedel, 2013;Tsuchiya et al, 2015;Wither et al, 2012).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…In a similar manner, hMeCP2 expression in 5-HT neurons also results in a loss of nighttime sleep, however, with the fine temporal resolution, we can identify sleep loss intervals that are both unique and overlapping when compared to hMeCP2 expression in OA neurons. Finally, in a previous study we determined that hMeCP2 expression in astrocytes non-cell-autonomously alters the sleep network only during distinct nighttime hours (Hess-Homeier et al 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Total RNA from each pool (∼35 heads/pool) was isolated by Tri-Reagent (Molecular Research Center, Cincinnati, OH, USA). The RNA samples were DNase treated and reverse transcribed as described previously (Hess-Homeier et al 2014). The qPCR reactions were carried out in quadruplicate for each gene and genotype on an Agilent Stratagene Mx3005P platform using following thermal protocol: 95 ∘ C -10 min; 40 × (95 ∘ C -30 seconds; 53 ∘ C -1 min; 72 ∘ C -1 min) followed by 0.5 ∘ C stepwise increment from 65 to 95 ∘ C. Cyclin-dependent kinase 2 (Cdc2c) reference gene was used for data normalization.…”
Section: Quantitative Reverse Transcription Polymerase Chain Reactionmentioning
confidence: 99%